The probiotic-induced disregulation of immune-related genes in colon cells and relation with colorectal cancer: Dysregulation of immune genes after probiotic treatment - Türk, Seyhan; Yılmaz, Ayşegül; Safari Baesmat, Ayriana; Malkan, Umit Yavuz; Ucar, Gulberk; Türk, Can (Cellular and Molecular Biology, 2023)
Supplemental probiotics available without a doctor's prescription have become a booming global market in past few years. Medical research has shown that probiotics may benefit both healthy people and cancer patients by improving their immune systems and digestive health. Even though they seldom produce serious side effects, it's important to note that they are generally safe to use. But further investigation into the role of probiotics and gut microbes in the etiology of colorectal cancer is required. Here we used computational methods to identify the transcriptome alterations induced by probiotic treatment of colon cells. The impacts of genes with substantially altered expression were assessed in relation to the progression of colorectal cancer. Following probiotic treatment, substantial and high-level changes in the expression of genes were determined. BATF2, XCL2/XCL1, RCVRN and, FAM46B were up-regulated while IL13RA2, CEMIP, CUL9, Cand XCL6, PTCH2 were down-regulated in probiotic-treated colonic tissue and tumor samples. Also, immune-related pathways were determined that contribute to colorectal cancer formation and progression, as well as genes with opposing roles. This suggests that the length and dosage of probiotic use, in addition to the specific bacterial strain, maybe the most important determinants in the association between probiotics and colorectal cancer.